Career Related Math Units. Teacher's Edition - Michalicek, Richard; Robbinsdale Independent School District 281, Minn. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
Individualized units of math instruction related to each of several occupations in 14 occupational clusters comprise the high school career-related math curriculum. An introductory booklet provides students with general information on the clusters; when students have selected an occupation that interests them, they take the packet of instructional materials for that occupation, complete the pretest, and, in conference with the teacher, decide whether to continue the unit or to concentrate first on any math skills in which the pretest has revealed a deficiency. Each instructional unit relates information about a career and about home management in a personalized narrative, which contains problems requiring specific math skills. The materials include facsimiles of forms used by persons employed in the occupation; the authors recommend supplementing these with actual source materials. Contained in the document are the students' introductory booklet, the kits of instructional materials, pretests and posttests, answer keys, a student record sheet, and recommendations for teachers on procedures. The materials were prepared by a team of Minnesota math teachers and a work experience coordinator, after their students identified the jobs in which they were most interested. The units present fictional persons pursuing occupations which follow traditional sex-role expectations. (Author/AJ)
Sponsoring Agency: Minnesota State Dept. of Education, St. Paul. Div. of Vocational and Technical Education.
ERIC Note: For related document, see CE 005 684.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Education; Career Exploration; Career Opportunities; Home Management; Individualized Instruction; Instructional Materials; Job Skills; Learning Activities; Mathematics Curriculum; Mathematics Education; Mathematics Instruction; Mathematics Materials; Noncollege Bound Students; Occupational Information; Secondary Education; Secondary School Mathematics; Simulation; Units of Study; Worksheets; Guides, General